Free Fatty Acids Profiles Are Related to Gut Microbiota Signatures and Short-Chain Fatty Acids - Rodríguez-Carrio, Javier; Salazar, Nuria; Margolles, Abelardo; González, Sonia; Gueimonde, Miguel; de los Reyes-Gavilán, Clara G.; Suárez, Ana (Frontiers in Immunology, 2017)
A growing body of evidence highlights the relevance of Free Fatty Acids (FFA) for human health, and their role in the crosstalk between the metabolic status and immune system. Altered serum FFA profiles are related to several metabolic conditions, although the underlying mechanisms remain unclear. Recent studies have highlighted the link between gut microbiota and host metabolism. However, although most of the studies have focused on different clinical conditions, evidence on the role of these mediators in healthy populations is lacking. Therefore, we have addressed the analysis of the relationship among gut microbial populations, short-chain fatty acid (SCFA) production, FFA levels and immune mediators (IFN, IL-6 and MCP-1) in 101 human adults from the general Spanish population. Levels of selected microbial groups, representing the major phylogenetic types present the human intestinal microbiota, were determined by quantitative PCR. Our results showed that the intestinal abundance of Akkermansia was the main predictor of total FFA serum levels, displaying a negative association with total FFA and the pro-inflammatory cytokine IL-6. Similarly, an altered FFA profile, identified by cluster analysis, was related to imbalanced levels of Akkermansia and Lactobacillus as well as increased fecal SCFA, enhanced IL-6 serum levels, and higher prevalence of subclinical metabolic alterations. Although no differences in nutritional intakes were observed, divergent patterns in the associations between nutrient intakes with intestinal microbial populations and SCFA were denoted. Overall, these findings provide new insights on the gut microbiota-host lipid metabolism axis and its potential relevance for human health, where FFA and SCFA seem to play an important role.